3M dwarfism: a study of two further sibs. Issue 9 (September 1989) - Feldmann, M; Gilgenkrantz, S; Parisot, S; Zarini, G; Marchal, C
Abstract : Two sibs are reported with clinical and radiological features of the 3M syndrome. The differential diagnosis is discussed, particularly with regard to Russell-Silver syndrome.